Seroprevalence of Newcastle Disease virus (NDV) antibodies in pigeons in selected areas in Klang Valley, Malaysia - Zaini, Nurfatin Shakira (2017)
Newcastle disease is a disease of domestic poultry and other bird species caused by Newcastle Disease virus from family of Paramyxoviridae. No study was done for NDV seroprevalence in pigeons compared to commercial chicken in Malaysia. Therefore, there is a need to do this preliminary seroprevalence study so that we able to know the prevalence of antibody level against NDV in pigeons and further, it is important for clinical measure such as they may serve as reservoirs of ND for galliformes group. Newcastle Disease (ND) can be transmitted by direct contact with diseased or carrier birds, fomites, hatching chicks from infected egg and also potential zoonotic disease. A total of 60 sera samples of pigeons were collected from two group of pigeons; wild and captive. Pigeons were sampled from several areas in Klang Valley. The sera had been analyzed for presence of antibodies against NDV using haemagglutination inhibition (HI) test. Out of sixty samples, 50.0% (30/60) samples were seropositive for NDV antibodies. Wild pigeons showed 41.7% (15/36) seroprevalence while captive pigeons with 62.5%(15/24) seroprevalence. This means that captive pigeons has higher seropositive compared to wild. In conclusion, this study proved that pigeons are exposed to Newcastle Disease virus at certain stage of their life and can develop antibodies against NDV. Further study should be done on virus detection and isolation from faeces, tracheal and nasal swabs to determine whether pigeons are reservoir and shedding the virus to the environment.